A theoretical review on the role of positive emotional classroom rapport in preventing EFL students’ shame: A control-value theory perspective - Kang, Chunxiao; Wu, Jianxiao (Frontiers in Psychology, 2022)
Background Second/foreign language teaching has been considered as a dialogic and interactive job in which teachers’ and students’ emotions and behaviors are closely connected to each other. When there is a harmonious and positive relationship between the teacher and students in the classroom, many favorable academic outcomes may emerge. A bulk of research has endorsed the power of positive emotional classroom rapport in EFL contexts. However, its role in preventing negative students’ emotions like shame, as an achievement emotion, in terms of perceived control and value tasks has rarely (if any) caught scholarly attention. Objective This study aimed to provide insights into the role of emotions in L2 education and the way students’ shame can be prevented or curbed in light of a positive emotional classroom rapport. Method/Design This article systematically reviewed the theoretical and empirical underpinnings of EFL teachers’ positive emotional classroom rapport and students’ shame in light of the control-value theory. Results In this research, it was asserted that by building a positive emotional classroom rapport EFL teachers can block and even eliminate students’ shame. Implications The study offers practical implications to EFL teachers, trainers, principals, and researchers by increasing their knowledge and abilities in managing psycho-emotional mechanisms and factors and enriching interpersonal aspects of EFL education.